Marking place new perspectives on early neolithic enclosures - Last, Jonathan (Oxbow Books, 2022)
Latest in the Neolithic Studies Group Seminar Papers series arising from the NSG conference of November 2019. This collection showcases and explores the wide range of current work on causewayed enclosures and related sites, and assesses what we still want to know about these sites in light of the monumental achievement of the seminal publication Gathering Time (2011). Papers comprise reports on recent development-led fieldwork, academic research and community projects, and the volume concludes with a reflection by the authors of Gathering Time. 0Much archaeological work is concerned with identifying gaps in our knowledge and developing strategies for addressing them; we perhaps spend less time thinking about how research should proceed when we already know, relatively speaking, quite a lot. The programme of dating causewayed enclosures in southern Britain that was published in 2011 as Gathering Time (Oxbow Books) gave us a new, more precise chronology for many individual sites as well as for enclosures as a whole, and as a consequence a far better sense of their significance and place in the story of the British Early Neolithic. Arguably causewayed enclosures are now the best understood type of Neolithic monument. Yet work continues, and in the last few years new discoveries have been made, older excavations published and further work undertaken on well-known sites. Viewing this research within the new framework for these monuments allows us to assess where our understanding of enclosures has got to and where the focus of future research should lie
Keywords: Wall; Neolithikum; Großbritannien; Neolithic period / Great Britain; Dwellings, Prehistoric / Great Britain; Earthworks (Archaeology) / Great Britain; Great Britain / Antiquities; Antiquities; Dwellings, Prehistoric; Earthworks (Archaeology); Neolithic period; Great Britain; Konferenzschrift -- 2019